x*2 - 6x + 9
x*2 -3x -3x +9
x(x-3) -3(x-3)
(x-3)(x-3)
Note also that x*2 - 6x + 9 is of the form a*2 -2ab + b*2 and so the factors are
(x-3) and (x-3)
2x2 - 9x + 4 = (2x - 1)(x - 4)
127 easy math people
81
= 90 (9*10)
9 + 9 + 9 + 9 + 9 + 9 + 6 + 6 + 6 + 6 + 2 + 2 + 23 + 3 + 3 + 4 + 4 + 4 = 123
It is: 3(t+3)
2x2 - 9x + 4 = (2x - 1)(x - 4)
-9(a + b)
It is possible to factorise 4x²-9 further.Factorising is to express a number or expression as a product of factors.The technique of factorising two terms: a² - b² = (a + b) (a - b)If we apply ( 4x²-9 ) to the previous technique: 4x² - 9 = (2x + 3) (2x - 3)
x(x-7)
9
That is 27 x 9 = 243
189
263
127 easy math people
The sum of 27 occurrences of the number 9 is calculated by multiplying 27 by 9, resulting in 243.
81